The surname structure of Trentino (Italy) and its relationship with dialects and genes. (3rd April 2021) - Boattini, Alessio; Bortolini, Eugenio; Bauer, Roland; Ottone, Marta; Miglio, Rossella; Gueresi, Paola; Pettener, Davide
Abstract: Background: Thanks to the availability of rich surname, linguistic and genetic information, together with its geographic and cultural complexity, Trentino (North-Eastern Italy) is an ideal place to test the relationships between genetic and cultural traits. Aim: We provide a comprehensive study of population structures based on surname and dialect variability and evaluate their relationships with genetic diversity in Trentino. Subjects and methods: Surname data were collected for 363 parishes, linguistic data for 57 dialects and genetic data for different sets of molecular markers (Y-chromosome, mtDNA, autosomal) in 10 populations. Analyses relied on different multivariate methods and correlation tests. Results: Besides the expected isolation-by-distance-like patterns (with few local exceptions, likely related to sociocultural instances), we detected a significant and geography-independent association between dialects and surnames. As for molecular markers, only Y-chromosomal STRs seem to be associated with the dialects, although no significant result was obtained. No evidence for correlation between molecular markers and surnames was observed. Conclusion: Surnames act as cultural markers as do other words, although in this context they cannot be used as reliable proxies for genetic variability at a local scale.